Seamless cloning and gene fusion - Lu, Quinn (Trends Biotechnol, 2005)
Gene fusion technology is a key tool in facilitating gene function studies. Hybrid molecules in which all the components are joined precisely, without the presence of intervening and unwanted extraneous sequences, enable accurate studies of molecules and the characterization of individual components. This article reviews situations in which seamlessly fused genes and proteins are required or desired and describes molecular approaches that are available for generating these hybrid molecules.